Safety and efficacy of direct oral anticoagulants in bioprosthetic valves: A systematic review and meta-analysis - Bakr, Lubna; Elsayed, Ahmed; Saleh, Omar; Abdalraouf, Mostafa; Ng, Ghulam André; Ibrahim, Mokhtar (Frontiers in Cardiovascular Medicine, 2023)
Background: Direct oral anticoagulants are efficient alternatives to vitamin K antagonists. There is little evidence regarding their use in patients who underwent bioprosthetic valve replacement whether surgically or through a transcatheter approach and have another indication of anticoagulation. Trials have compared different members of the DOACs family to VKAs and showed that they were at least non-inferior to VKAs with regard to safety and efficacy. However, this is still controversial. Our meta-analysis aims at providing a clearer view of their future use in this subgroup of patients. Methods: PubMed and Cochrane were searched for randomised clinical trials and observational studies. Bleeding, stroke, and all-cause mortality were the outcomes of interest. Results: Ten papers with a total of 4088 patients were included. Our meta-analysis revealed no significant differences between the incidence of bleeding between DOACs and warfarin (16% vs 17%, OR=0.94, 95% CI [0.56-1.57], p=0.81, I2 =81%). No statistical difference was found in stroke between both groups (2.5% vs. 3.3%, OR=0.75, 95% CI [0.41-1.38], p=0.36, I2=35%). All-cause mortality was not statistically significant between both groups (9.2% vs. 13.7%, OR=0.85, 95% CI [0.68-1.07], p=0.16, I2=56%). Interestingly, subgroup analysis of randomised controlled trials and prospective studies favoured DOACs with lower risks of both bleeding and stroke. Conclusion: Direct oral anticoagulants appear to be at least as safe and effective as VKAs in patients with bioprosthetic valves and another indication of anticoagulation. There could be potential benefit from the use of DOACs; however, further evidence is required.